Geology and Petrography of the Northern Yamato Mountains, East Antarctica (Earth Sciences) - SHIRAISHI, Kazuyuki (1977)
P(論文) In the northern Yamato Mountains, there are two groups of rocks. One is the syenite gneiss group which was metamorphosed under the granulite facies conditions. The other is the granite gneiss group which was metamorphosed under the amphibolite facies conditions. Besides, metabasites and acid dykes are found to accompany them. There is gradational transition between the two groups of the rocks, and it is revealed from the field and microscopic observations that the transition is not progressive metamorphism but the early-formed syenite gneiss was activated under the amphibolite facies conditions resulting in the granite gneiss. According to the bulk chemical analysis the trend of the granitization in the diagram, norm q-or-ab-ne, is characterized by the decrease of "or" and the increase of "q". Finally the point of eutectic minimum is reached. Therefore, it seems evident that the granitization occurred in association with anatexis. departmental bulletin paper